Pengaruh Serangan Rushing Terhadap Protocol Ad Hoc On Demand Distance Vector (AODV) pada Jaringan Mobile Ad Hoc Networks (MANET) - Eldyto Puspa Laksana; Reza Andria Siregar; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Ad Hoc Networks (MANET) is one type of wireless network that exists today, where mobile nodes are associated with unplanned or called ad hoc. There are various types of routing protocols on MANET and one of them is reactive routing. One example of reactive routing algorithms is Ad hoc On-Demand Distance Vector (AODV). Rush attacks use RREQ on route discovery to become a connecting node between the source and destination data packets on the network. The number of nodes used is 30 nodes, 40 nodes, 50 nodes. The simulation was carried out using Network Simulator (NS-2.35). Rush attacks have an impact on routing the AODV protocol by reducing its performance. It is proven by the value of the packet delivery ratio, packet loss, throughput, and end to end delay, which decreases in quality. The biggest decrease occurred in the implementation of 4 rushing attacks, there was a decrease in quality where packet delivary ratio at 40 nodes decreased by 12.90%, packet loss at 40 nodes increased by 12.90%, throughput at 40 nodes decreased by 18.27 kbps, and end to end delay on 30 nodes increased by 4035.3259 ms. Compared to experiments on 30 nodes and 50 nodes the quality loss is very small and there tends to be no decrease.